A high EMS daisy-chain SPI interface for battery monitor system *Project supported by the National Natural Science Foundation of China (No. 61334003). (March 2017) - Zhang, Qidong; Yang, Yintang; Chai, Changchun
Abstract: A high EMS current-mode SPI interface for battery monitor IC (BMIC) is presented to form a daisychain bus configuration for the cascaded BMICs and the communication between the MCU and master BMIC. Based on analog and digital mixed filtering technique, the proposed daisy-chain can avoid the isolated communication issue in electromagnetic interference environment, and reduce the extensively required I/O ports of MCU, at the same time reduce the system cost. The proposed daisy-chain interface was introduced in a 6-ch battery monitor IC which was fabricated with 0.35 μ m 30 V BCD process. The measurement result shows that the presented daisy-chain SPI interface achieves better EMS performance with different EMI injection while just consuming a total operation current up to 1 mA.